The effect of a cognitive dual-task on the control of wheelchair propulsion. - Leon Salm; Lucas Schreff; Christian Benker; Rainer Abel; Roy Müller (PLoS ONE)
Movement analyses of wheelchair users are rarely integrated into clinical operations, although these are recommended to prevent pain and injury in the upper extremity. In addition, previous movement analyses in the laboratory do not include the possible influences of distractions that occur in everyday wheelchair use. We therefore transferred the dual-task method known from the motion analysis of walkers to the analysis of the propulsion behavior of wheelchair users and examined whether the changes resulting from the additional cognitive task also show up here. The 52 participants consisted of 38 manual wheelchair users (age = 43.8 ± 14.2 years; sex = 11/27 f/m) and 14 novices (age = 39.2 ±  15.4 years; sex = 8/6 f/m). The participants propelled their wheelchairs on a test stand and movements of hand and wheel were recorded with a marker-based 3D motion-capturing system. The measurements were performed at preferred speed under single- and dual-task conditions. The Paced Auditory Serial Addition Test (PASAT) was used for the additional cognitive task. The participants propelled with a significantly higher frequency (p = 0.001), had a shorter cycle- (p = 0.001) and recovery time (p = 0.001) and propelled with a lower push angle (p = 0.045) under dual-task conditions. The distance between the hand and the pushrim was shorter (p = 0.008) and the distance between the hand and the axis was significantly longer (p = 0.004). The differences occurred predominantly in the group of manual wheelchair users. Significant differences in propulsion behavior were also found between the two groups under both single-task and dual-task conditions. The results indicate that dual-task conditions during wheelchair propulsion have an influence on spatiotemporal parameters similar to walking. Future movement analyses of wheelchair users should therefore consider the additional measurement under dual-task conditions in order to obtain more realistic results.